BENTUK PENYAJIAN TARI JEPIN LANGKAH BUJUR SERONG DI KOTA PONTIANAK KALIMANTAN BARAT - Lissa Maharani; Imma Fretisari; Regaria Tindarika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the presentation form of the Jepin Langkah Bujur Serong dance of Pontianak, West Kalimantan, as well as to complete the research data. The focused problem is related to the elements of presentation form of the dance. Qualitative descriptive method was applied in the study, with qualitative form and the use of choreography approach. The data was collected by observation, interview and documentation of the Jepin Langkah Bujur Serong as an entertainment dance. The dance is performed by 4 to 10 dancers of both men and women. It has 3 variation of movement: the beginning, the middle and the end, which are known as ragam 1, ragam 2 and ragam 3. Tahto movement is used in every change of the ragam. The floor patterns of the dance can also be adjusted creatively. Musical instruments played to perform the dance are selodang, gambus, beruas, accordion and violin. Realist makeup and the Malay’s traditional clothes of Pontianak are used in performing this dance.Keyword: Form of presentation of the Jepin Langkah Bujur Serong dance